2018
DOI: 10.1111/ane.12996
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 G2019S Parkinson's disease with more benign phenotype than idiopathic

Abstract: In this study, G2019S carriers had a more benign phenotype than non-carriers. Cognitive impairment and depression were less common in G2019S male carriers compared with females. In addition, we found that LRRK2 gene dosage does not influence the severity of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
2
16
3
Order By: Relevance
“…In our study, patients with the G2019S mutation had a mean AAO of ~52 years, a high proportion of patients with late AAO (>50 years), a good response to levodopa, a predominance of tremor as a first symptom of PD, about a quarter had cognitive impairment, about 10% had dysautonomia, but no other atypical signs after a mean disease duration of ~10 years. Although the clinical features of the LRRK2 Gly2019Ser carriers compared with patients with idiopathic PD in literature are conflicting [meta-analysis in ( 25 )], even for the same ethnic PD population [i.e., of North-African origin; ( 26 31 )], our data are consistent with those of 724 LRRK2 mutation carriers listed in the MDSGene database. Like LRRK2 mutation carriers, VPS35 Asp620Asn carriers had a phenotype very similar overall to that of idiopathic PD: absence of atypical signs, excellent levodopa response, normal cognition, and absence of neuropsychiatric features.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, patients with the G2019S mutation had a mean AAO of ~52 years, a high proportion of patients with late AAO (>50 years), a good response to levodopa, a predominance of tremor as a first symptom of PD, about a quarter had cognitive impairment, about 10% had dysautonomia, but no other atypical signs after a mean disease duration of ~10 years. Although the clinical features of the LRRK2 Gly2019Ser carriers compared with patients with idiopathic PD in literature are conflicting [meta-analysis in ( 25 )], even for the same ethnic PD population [i.e., of North-African origin; ( 26 31 )], our data are consistent with those of 724 LRRK2 mutation carriers listed in the MDSGene database. Like LRRK2 mutation carriers, VPS35 Asp620Asn carriers had a phenotype very similar overall to that of idiopathic PD: absence of atypical signs, excellent levodopa response, normal cognition, and absence of neuropsychiatric features.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study conducted in South Africa found that 8 out of 647 patients screened were G2019S-carriers but all are of Ashkenazi Jewish origin except one (whose grandfather was German) (49). In a study on African Arabic patients in Tunisia, G2019S-carriers had similar PD symptoms to non-G2019S idiopathic PD cases but had a younger age at onset (AAO), a more benign phenotype and less cognitive impairment (59). In the South African study, the average AAO of the eight G2019S carriers was 56.6 years (SD 10.9), they had typical PD symptoms, and the homozygous mutation carrier did not exhibit a more severe disease to the others, although two patients had severe lower limb dystonia (49).…”
Section: Genetics Of Pd In African Populationsmentioning
confidence: 99%
“…Interestingly, the G2019S mutation is more frequently associated with LB pathology compared to other LRRK2 mutations [ 88 ]. In terms of the severity of disease, there was no gene dosage effect observed, and G2019S carriers showed a more benign disease course [ 89 ]. In terms of biological readouts, some limited information is available from the analysis of biosamples from G2019S carriers.…”
Section: Understanding Lrrk2 In Pd Through the Study Of Disease-linked Or Associated Variants Of Lrrk2mentioning
confidence: 99%